Analisis Self-Efficacy Calon Guru Sekolah Dasar melalui Kegiatan Microteaching - Anne Alfine Nainggolan; Enisa Simamora; Juliana Simanjuntak; Yohanna Angelia; Nurmayani Nurmayani (Jurnal Merah Putih Sekolah Dasar, 2026)
This study aimed to analyze the self-efficacy of prospective elementary school teachers through microteaching activities. The study employed a descriptive quantitative approach involving 40 students of the Elementary School Teacher Education Program (PGSD), class of 2023, as research participants. Data were collected through a closed-ended questionnaire and analyzed using descriptive statistical techniques in the form of percentages. The findings revealed that microteaching activities contributed positively to the improvement of students' self-efficacy. This was indicated by students' confidence in developing lesson plans (62.5%), speaking in front of the class (67.5%), utilizing learning media (67.5%), and conducting learning evaluations (72.5%). In addition, repeated teaching practice and constructive feedback from lecturers and peers helped students enhance their confidence and teaching readiness. These findings indicate that microteaching serves as an effective learning strategy for strengthening the self-efficacy of prospective elementary school teachers and preparing them for real classroom teaching situations.